Multi-frequency multi-mode ultrasound treatment for removing pesticides from lettuce (Lactuca sativa L.) and effects on product quality. (May 2021) - Azam, S M Roknul; Ma, Haile; Xu, Baoguo; Devi, Shoma; Stanley, Sarah L.; Siddique, Md Abu Bakar; Mujumdar, Arun S.; Zhu, Junsong
Abstract: This article presents the efficacy of multi-frequency (20, 40, and 60 kHz) multi-mode ultrasound treatment (MFMU) in sequential and simultaneous combination for the removal of abamectin b1 (AB), alphamethrin (AL), and emamectin benzoate (EB) from fresh lettuce surface. UHPLC-MS/MS was used to determine the effectiveness of the water wash and ultrasonic cleaning methods based on the pesticide reduction level. The most effective treatment for removing the pesticides was found to be the triple-frequency sequential mode (TSQ), which removed 92.31, 89.36, and 95.25% of AB, AL, and EB, respectively, after 8 min of ultrasonication. The effects of ultrasound on the physiological and nutritional properties suggest that the TSQ treated lettuce quality is comparable to that of the water washed produce based on the total chlorophyll and total carotenoid contents. Scanning electron microscope observations reveal that TSQ results in the least lettuce surface damage. Furthermore, the studied optimal condition retained better overall color ( ΔE ) and greenish appearance than other treatments. The application of MFMU in a sequential mode to remove pesticide residues from lettuce is found to be a promising vegetable-cleaning method without compromising product integrity and quality. Highlights: Effect of 20, 40, and 60 kHz ultrasound for removing pesticides from lettuce was studied. Ultrasonication could remove pesticides and make product safe for consumption. Triple-frequency sequential mode could remove maximum 95.25% of the pesticide. Sequential ultrasonication is more effective than simultaneous. Triple-frequency ultrasound cleaning of lettuce retains the fresh-like properties of lettuce.